NATIONAL BREAD PRODUCTS - Nazarova Lobar Xolovna (Web of Journals Publishing, 2025)
This article highlights national bread products, which hold a special place in the traditional food culture of the Uzbek people, as well as their technological processes. It provides information about the characteristics, composition of raw materials, preparation technology, and storage methods of various types of bread specific to different regions, such as patir, obi-non, tandir non, qatlama, and other products. Furthermore, the article analyzes the role of bread products in nutrition, their biological and energetic value, and the directions for improving production based on modern technologies. The article is aimed at preserving national traditions, enhancing the quality of bread products, and exploring opportunities for industrialization.
Keywords: National bread, bread products, bread technology, tandir bread, patir, qatlama, traditional food, flour products, food technology, bread quality.